2011
DOI: 10.1089/acm.2010.0082
|View full text |Cite
|
Sign up to set email alerts
|

Manual Acupuncture for Relieving Pain Associated with Panretinal Photocoagulation

Abstract: Acupuncture might help reduce pain during PRP treatment. However, further randomized studies are necessary to verify these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The investigators concluded that Entonox can be used as a safe and effective analgesic agent during PRP treatment [3]. The feasibility of manual acupuncture for reducing pain during PRP treatment was also investigated in a prospective, comparative nonrandomized study and was found to be helpful [12]. In a recent published randomized controlled trial, single spot short duration time (20 ms) was compared with conventional laser therapy as another option for diabetic retinopathy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that Entonox can be used as a safe and effective analgesic agent during PRP treatment [3]. The feasibility of manual acupuncture for reducing pain during PRP treatment was also investigated in a prospective, comparative nonrandomized study and was found to be helpful [12]. In a recent published randomized controlled trial, single spot short duration time (20 ms) was compared with conventional laser therapy as another option for diabetic retinopathy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Only one article (Chiu & Wu, 2011) was returned; this article described a prospective, comparative, nonrandomized study conducted in a Taiwanese hospital. The sample consisted of 34 patients diagnosed with proliferative DR, including 18 patients allocated to the experimental group (EG) and 16 patients allocated to the control group (CG).…”
Section: Is There Evidence Of Efficacy Of Nonpharmacological Intervenmentioning
confidence: 99%
“…For example, a systematic review suggested that acupuncture can relieve acute postoperative pain after back surgery [6]. Another study suggested that acupuncture may help reduce pain during panretinal photocoagulation treatment [7]. Several clinical studies have shown that acupuncture may be effective in improving postoperative analgesia, reducing intraoperative anesthetic requirements and immunosuppression, and reducing the incidence of anesthesia-related side effects [8,9].…”
Section: Introductionmentioning
confidence: 99%